PERANCANGAN ALAT BANTU ANGKUT MANNEQUIN UJI COBA KENDARAAN MILITER (STUDI KASUS : PT. PINDAD) - Wibawa, Zaidan Mufid; Adiluhung, Hardy; Chalik, Chris (eProceedings of Art & Design, 2024)
Abstract : This research is motivated by a direct review that occurred in the field during the trial activities at PT. Pindad, namely the inefficiency of the mannequin transfer process because the transfer still uses a time-consuming dismantling and reassembly process because it does not allow the use of a hydraulic jack to transport the machine, because the field trial field does not match the specifications of the machine jack which has limited specifications. Therefore, the researcher had the idea to create a special tool for the purpose of moving the vehicle trial mannequin that adopts a similar system or mechanism more efficiently. The purpose of this study is to design a vehicle trial mannequin transport tool that can support efficient trial needs with a compact size. The method used in this study is a qualitative method, through this descriptive analysis will help the author to summarize and interpret the data obtained in a systematic and objective manner. Keywords: transport, mannequin, transportation, military